Agricultural Biotechnology Research and Development in the Philippines: The Need for a Strategic Approach - Saturnina C. Halos (Philippine Institute for Development Studies (PIDS), 2000)
This paper examines the capacity of the Philippines to join and benefit from the biotechnological revolution. It reviews world trends and issues and Philippine agricultural biotechnology R&D contents, directions and management using published literature, annual reports, symposia proceedings, thesis manuscripts, papers written by individuals, project listings provided by pertinent agencies, and limited field visits and interviews. The paper has three parts. Part I presents the scope of biotechnology applications in agriculture. Part II discusses world trends and issues in biotechnology. Part III presents the state of the art in and an analysis of agricultural biotechnology R&D in the Philippines.
Keywords: 330; genetic engineering; plant breeding; Grüne Gentechnik; Technologiepolitik; Philippinen